Methodology for the Assessment of Spatial Economic Impacts of Transport Projects and Policies - Johannes Brocker; d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2001)
In this study we develop an integrated econometric and CGE modelling framework for transport projects and transport policies at the European level by integrating network, regional economic and macro-economic impacts. The paper presents the formal structure of the integrated econometric and CGE modelling framework, explains the calibration and applies it to the policy evaluation. The effects of infrastructure investments are modelled by simulating trade cost changes in a comparative static analysis, using estimates of trade cost changes due to new infrastructure links, obtained from a transport network model. By performing a systematic and quantitative analysis of the spatial, network and socio-economic impacts of transport investments and policy and carrying out scenario simulations we improve the under-standing of the impact of transportation policies on short- and long-term spatial development in the EU.
Keywords: C68; D58; O41; R13; 330; Transport Policy; Impact analysis; Spatial CGE Model